Peran Project Owner dalam Menjalankan Agile Project Management (Studi Kasus: PT. XYZ) - Fernanda Rachmadini; Sugeng Santoso (Jurnal Manajemen dan Organisasi, 2021)
Agile project management methodologies provide the means to respond to highly dynamic customer needs. One of the agile project management frameworks is scrum. Scrum is shaped in 3 important roles by project owner, scrum master, and development team. The research objective was to determine the roles and responsibilities of the project owner when run several projects at PT. XYZ using the agile project management methodology scrum framework. The research method used is descriptive qualitative, with the investigative method adopted is a single case study, namely the company PT. XYZ which is engaged in IT with several application development projects. The results obtained from the interview are that the role of the project owner must understand the needs desired by customers by being sensitive to customer needs that highlight quality and uncertain changes, besides understanding the scrum team in delivering product services desired by customers in order to provide maximum quality and acceptance by the customer. In addition, the project owner must carry out the responsibilities such as explaining the SoW and the objectives to be achieved in the project, preparing a budget for the project, allocating of development teams who will work on the product, determining the priority of the product backlog and the sprint that will be executed, monitoring each stage sprints that are being worked on by the developer team, holding daily meetings for a maximum of 15 minutes with the scrum team, arranging and holding meetings with customers and the scrum team for each sprint that has been completed, and collaborating with the scrum team to discuss any changes desired by customers.